1999
DOI: 10.1016/s0304-405x(99)00006-9
|View full text |Cite
|
Sign up to set email alerts
|

Conditional market timing with benchmark investors

Abstract: This paper tests models of mutual fund market timing that allow the manager's payo! function to depend on returns in excess of a benchmark, and distinguish timing based on publicly available information from timing based on "ner information. We simultaneously estimate parameters which describe the public information environment, the manager's risk aversion, and the precision of the fund's market-timing signal. Using a sample of more than 400 U.S. mutual funds for 1976}94, our "ndings suggest that mutual funds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(27 citation statements)
references
References 34 publications
(17 reference statements)
1
23
1
2
Order By: Relevance
“…The findings of Dahr and Mandal run counter to those earlier established by Becker et al (1999) on the evidence of market timing skills from active mutual fund managers. They made a distinction between timing based on publicly available information which can be captured by some instrumental variables and timing based on better information.…”
Section: Introductioncontrasting
confidence: 99%
“…The findings of Dahr and Mandal run counter to those earlier established by Becker et al (1999) on the evidence of market timing skills from active mutual fund managers. They made a distinction between timing based on publicly available information which can be captured by some instrumental variables and timing based on better information.…”
Section: Introductioncontrasting
confidence: 99%
“…Mutual fund holdings are also used in a range of studies evaluating fund performance including, for example, Titman (1989,1993), Wermers (1999Wermers ( , 2000Wermers ( , 2004, and Ferson and Khang (2004): these show that measures based on holdings data are more powerful in detecting mutual fund stock selection ability. Finally, we note that several studies look at the portfolio allocation between cash and equity components to measure market timing and find little evidence of such timing skill (see for example Becker, Ferson, Myers, and Schill, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Some research also shows that mutual funds not managed to "timing the market" (Treynor and Mazuy, 1966;Henriksson, 1984;and Becker et al, 1999). Meanwhile, Sinclair (1990) to evaluate market timing and stock selection, the first in Australia, found that inversely with market timing in mutual funds would reduce the profitability of stock selection.…”
Section: Literature Reviewmentioning
confidence: 99%